Controlling droplet splashing and bouncing by dielectrowetting - Quetzeri-Santiago, MA; Castrejón-Pita, JR; Castrejon Pita, AA (Springer Nature, 2021)
Stopping droplets from bouncing or splashing after impacting a surface is fundamental in preventing cross-contamination, and the spreading of germs and harmful substances. Here we demonstrate that dielectrowetting can be applied to actively control the dynamics of droplet impact. Moreover, we demonstrate that dielectrowetting can be used to prevent droplet bouncing and suppress splashing. In our experiments, the dielectrowetting effect is produced on a flat substrate by two thin interdigitated electrodes connected to an alternating current potential. Our findings show that the strength of the electric potential can affect the dynamic contact angle and regulate the spreading, splashing and receding dynamics at the right time-scales.